The ethical subject in the educational justice - Mónica Laura Fornasari (Ministerio de Educación, Dirección General de Educación Superior, 2017)
This research emerges from the institutional coexistence present difficulties that affect the youth participation ways in the educational environment when youngsters cannot internalize the legalities as an education principle. The disagreements with educators, when taking part from the discipline paradigm, does not allow developing a learning experience about the relationship between alterity and citizenship. We were able to understand, by means of our goals, based on the complexity educational field, the Ethical Subject constitution and their subjectivity ways in building an educational justice. We carried out a qualitative study based on a hermeneutic position and focused in two public secondary schools- as a case study- specifically with a clinic focus. We analyzed a subjective dimension in sixth course students. The accomplished results from this research allow deep en and complete Coexistence School Agreements (AEC in Spanish) evaluative studies and their impact in the Subjectivity Educational Policies. When school trains subjects to elaborate and solve conflicts, it promotes the symbolic processes development and develops in educational intervention devices, promoting the democratic building of scholar experience and justice. In conclusion, we assert that our youngster's socio pedagogic integration can be implemented thanks to an educational justice culture at a school scene